A new way for revealing the damage evolution of impacted CFRP laminate under compression-compression fatigue load based on thermographic images. (15th September 2017) - Li, Yin; Zhang, Wei; Ming, An-bo; Yang, Zheng-wei; Tian, Gan
Abstract: A new way is proposed in this work to reveal the damage evolution law of impacted carbon fiber reinforced polymer (CFRP) laminate under compression-compression fatigue load based on thermographic images. Firstly, several specimens are began with impact testing with different energies, followed by compression-compression fatigue testing with different load amplitudes and monitored by infrared camera. Then, the thermographic images gathered by infrared camera are analyzed. Finally, the damage area is introduced to quantitatively reveal the damage evolution law of these impacted specimens. The obtained results show that combining appropriate image processing methods, the damage area can be used as an effective damage index to quantitatively reveal damage evolution law of impacted CFRP laminate under compression-compression fatigue load with excellent accuracy.